Pemahaman Hadis Tentang Moderasi Beragama (Studi Takhrij Hadis) - Askar, Nurlacksmi Septiana; Tasbih, Muh. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
From the public to religious leaders, religious moderation has become a widespread phenomenon lately. This has to do with the religious climate in Indonesia, which is a bit unsettling. This is an example of religious radicalism, as the increasing religious polemics have a significant impact on elements of harmony. This situation encourages the development of religious moderation. Religious moderation can be defined as religious practice that is balanced rather than excessive. However, over time the definition of religious moderation has become more complex. This thesis aims to find out whether Hadith as the second Muslim guideline has roots and has great potential to invite its followers to commit violence and terror, especially against people of other religions. In this study, researchers used the thematic method (Maudhu'i), which is to do takhrij Hadith regarding religious moderation, then sanad criticism and matan criticism. Then relate it to the contexts related to the problem studied. The results show that the Hadith does not invite Muslims to be violent, extreme and excessive in religion as well as the Qur'an. The Qur'an and Hadith offer that understanding and practicing religion must go through the path of balance and be in the middle ground so that religion seems friendly, gentle and compassionate. In fact, balance is a necessity, including in natural law as the harmony of life. If not, this world will be destroyed and perish.